Fault Tolerant Control of Attitude Dynamics of Nanosatellites - Guler, Demet Cilden; Hajiyev, Chingiz; Dasdemir, Janset (IEEE, 2017)
In this paper, fault-tolerant active control of the rotational motion of the satellite has been applied. Satellite mathematical models are introduced, and the nontraditional Kalman filter is designed with the presented control algorithms. Re-adjustment control procedure has been established taking into account the identified control distribution matrix. If there are three-axis reaction wheels on the satellite, the failure of one actuator, control setting is carried out using control distribution matrix diagnostics. Extended Kalman Filter has been introduced to control the distribution estimation of matrix elements, so check back adjustment rule is applied by the fault tolerant attitude control.
Keywords: nanosatellite; fault tolerant control; reconfigurable control; estimation; attitude; RECONFIGURABLE FLIGHT CONTROL; 2-STAGE KALMAN FILTER; Engineering; Remote Sensing